Ionizing Radiation-Induced GDF15 Promotes Angiogenesis in Human Glioblastoma Models by Promoting VEGFA Expression Through p-MAPK1/SP1 Signaling - Park, Hyejin; Nam, Ki-Seok; Lee, Hae-June; Kim, Kwang Seok (Frontiers in Oncology, 2022)
Glioblastoma multiforme (GBM), the most aggressive cancer type that has a poor prognosis, is characterized by enhanced and aberrant angiogenesis. In addition to surgical resection and chemotherapy, radiotherapy is commonly used to treat GBM. However, radiation-induced angiogenesis in GBM remains unexplored. This study examined the role of radiation-induced Growth/Differentiation Factor-15 (GDF-15) in regulating tumor angiogenesis by promoting intercellular cross-talk between brain endothelial cells (ECs) and glioblastoma cells. Radiation promoted GDF15 secretion from human brain microvascular endothelial cells (HBMVECs). Subsequently, GDF15 activated the VEGFA transcriptional promoter in the human glioblastoma cell line U373 through p-MAPK1/SP1 signaling. The upregulation of vascular endothelial growth factor (VEGF) in U373 cells resulted in the activation of angiogenic activity in HBMVECs via KDR phosphorylation. The wound healing, tube formation, and invasion assay results revealed that the conditioned medium of recombinant human GDF15 (rhGDF15)-stimulated U373 cell cultures promoted the angiogenic activity of HBMVECs. In the HBMVEC-U373 cell co-culture, GDF15 knockdown mitigated radiation-induced VEGFA upregulation in U373 cells and enhanced angiogenic activity of HBMVECs. Moreover, injecting rhGDF15-stimulated U373 cells into orthotopic brain tumors in mice promoted angiogenesis in the tumors. Thus, radiation-induced GDF15 is essential for the cross-talk between ECs and GBM cells and promotes angiogenesis. These findings indicate that GDF15 is a putative therapeutic target for patients with GBM undergoing radio-chemotherapy.